Hybrid Iterative Fourier Transform and Convex Optimization for Pattern Synthesis of Sparse Linear Arrays - Xie, Qi; Chen, Bo; Lin, Zhipeng; Lei, Shiwen; Zhang, Yinghao; Xu, Jun (2021 International Conference on Microwave and Millimeter Wave Technology (ICMMT), 2021)
The paper deals with the peak sidelobe level (PSLL) suppression problem with sparse linear array antenna. Firstly, the iterative Fourier transform (IFT) algorithm is utilized to optimally selected a thinned linear array which would meet the predetermined fill factor. With the first-order Taylor expansion of the far field with respect to the element position, the original optimization problem is converted to be convex. Then, the element positions of the thinned arrays are further optimized via a convex optimization algorithm. Compared with the existing method, the proposed one can greatly improve the sidelobe performance. Numerical results indicate the proposed method is effective for sparse array synthesis with low PSLL.